Estudo e desenvolvimento de antena de microfita aplicada à veículos aéreos não tripulados para inspeção em linhas de transmissão - Pereira, Thomas Tadeu de Oliveira (Universidade Federal Rural do Semi-Árido, 2018)
In wireless communications, there is a growing need for more compact and portable systems. In this context, research related to the development of antennas has intensified in recent years, especially those related to microstrip antennas, since these have unique properties as well as several applications. In this work, two different antenna configurations were designed, an array of microstrip antennas for the transmitting device and a single element with an omnidirectional pattern for the receiver, according to the needs of the application. The antennas are designed by the Transmission Line Theory according to the frequency of radio operation and the electrical and physical properties of the substrates used. The results were obtained through simulations in the ANSYS HFSS® software, and the best results were used to fabricate the devices in order to validate the simulations performed. The results of the simulations reached the characteristics of the application, as the return losses of both antennas were in accordance with the frequency band of the application in the band ISM in 2.4 GHz, with respect to the behavior of the radiation, the antenna proposed to the transmitter had a gain of 6.1 dB, approximately three times greater than the commonly used dipole / monopole antenna. The experimental result of the loss of return was shown to be in agreement with the simulated standard, in spite of the frequency displacement, both antennas constructed were suitable for application in the radio control of the UAV, having the microstrip array 7.5 MHz of bandwidth in the band of application and the simple element proposed to the 58.5 MHz receiver. The antennas were then implemented in the radiofrequency system and a range test was performed in order to verify the communication of the devices, presenting satisfactory results. Thus, a flight is performed via software for visual inspection of transmission lines, aiming the collection of images for analysis
Keywords: Antenas de microfita; VANT’s; Inspeção visual em linhas de transmissão; Microstrip antennas; UAV's; Visual inspection in transmission lines; ENGENHARIAS::ENGENHARIA ELETRICA